PERPUSTAKAAN, PUSTAKAWAN DAN TEKNOLOGI INFORMASI (Tiga Tiang Utama Sebagai Pendukung Sumber belajar) - Yendri Yendri (UIN Imam Bonjol Padang, 2017)
Learning resource center is a unit within an institution (specifically schools / universities / companies) that has an important role in encouraging the effectiveness and optimization of the learning process, and the implementation of various service functions (such as media services, training, learning consultancy, etc.). Improving learning productivity, providing the possibility of learning that is more individual in nature, providing a more scientific basis for learning, further strengthening learning, enabling learning instantly and enabling the presentation of broader learning, by presenting information that is able to penetrate geographical boundaries. In supporting these activities, libraries need to have library staff. According to Law No.43 of 2007, library staff is divided into two, namely technical staff and librarians. Library technical staff are non-librarians who technically support the implementation of library functions, for example computer technical staff, audio-visual technical staff and administrative technical staff. Library competence in the application of Information Technology has greatly changed the social character of the wearer. Changes in information needs, in interacting with others, in competition, and others. Learning needs also do not have to be seen as something solely serious